The Impact of Globalisation on the Sustainability of Local Cultural Identity in Indonesia - I Gusti Made Sumadi (Bali Tourism Journal, 2025)
Globalisation has become a pervasive force shaping cultural, social, and communicative processes across the world, profoundly influencing the sustainability of local cultural identities. In Indonesia, a country characterised by extensive cultural diversity, globalisation interacts with complex socio-cultural structures formed by ethnic plurality, indigenous traditions, and national ideology. This study aims to examine how globalisation affects the sustainability of local cultural identity in Indonesia, with particular attention to the roles of media, technology, education, and younger generations. Employing a qualitative descriptive approach based on a systematic literature review, this research synthesises peer-reviewed academic studies published between 2018 and 2024 that address globalisation, cultural identity, media influence, and youth cultural dynamics. The findings indicate that globalisation generates both disruptive and transformative effects on local cultural identity. On the one hand, the dominance of global media, consumer culture, and digital platforms contributes to cultural homogenisation, shifts in value systems, and declining engagement with traditional cultural practices, especially among Generation Z. On the other hand, globalisation also enables processes of cultural hybridisation, localisation, and creative adaptation, allowing local communities to reinterpret global influences while maintaining core cultural values. Digital media emerge as a paradoxical space that simultaneously accelerates global cultural diffusion and provides strategic opportunities for cultural preservation and innovation. The study concludes that local cultural identity should be understood as a dynamic and adaptive construct rather than a static heritage. Strengthening cultural education, enhancing media literacy, empowering traditional arts, and actively engaging younger generations are essential strategies for ensuring cultural sustainability.